Evaluation of mechanical and vibration behavior of hybrid epoxy carbon composite beam carrying micron-sized CTBN rubber and nanosilica particles. (September 2019) - Senthamaraikannan, C; Ramesh, R
The suppression of vibration in dynamic structures is considered as one of the important functional requirements. In the present investigation, the free vibration behaviour of the woven carbon-epoxy composite beams was studied by blending nanosilica and micro-sized carboxyl-terminated butadiene acrilonitrile copolymer CTBN rubber in an epoxy matrix. The basic I and channel shapes widely used in structural applications were considered for fabrication of composite beams and made by hand layup method. The hybrid specimens were prepared by keeping 9% rubber particles by weight as stable primary ingredients in epoxy and the secondary reinforcement nanosilica was added by varying the weight fraction of 6% and 11%. The mechanical behaviour study and free vibration test were conducted as per ASTM standards and compared between virgin and hybrid composites. The addition of nanosilica, as secondary reinforcement in an epoxy matrix improves the mechanical properties of CTBN rubber-blended carbon composites. The structural beams were tested by impulse frequency response method under cantilever boundary conditions. Frequency response function plots were recorded and compared for all considered beam samples. The decreased amplitude response observed in frequency response function plot for micro rubber added samples of 9 wt%, indicate enhanced passive damping characteristics. The nanosilica, along with the micro rubber particles, shows improved passive damping capacity than virgin carbon composite beam. Finite element modelling of the composite beam was done for modal response using ANSYS® application software. Mode shapes and corresponding modal frequency of all types of beams have been compared and discussed.